Linc00152 promotes proliferation in gastric cancer through the EGFR-dependent pathway. Issue 1 (December 2015) - Zhou, Jianping; Zhi, Xiaofei; Wang, Linjun; Wang, Weizhi; Li, Zheng; Tang, Jie; Wang, Jiwei; Zhang, Qun; Xu, Zekuan
Abstract Background Linc00152 has been identified highly associated with the tumorigenesis and development of gastric cancer, however, the detailed mechanism of Linc00152 involved still remains unclear. Methods RT-PCR and western blot were used to detect the expression of Linc00152 and EGFR. The CCK8 and EDU assay was employed to measure cell proliferation while xenotransplantation technology was applied in BALB/C nude mice. The interaction between lncRNA and target protein was investigated by RNA pull-down and RNA immunoprecipitation assay. Results In this study, we first confirmed the upregulation of cytoplasmic expressed Linc00152 in 72 pair tissues of gastric patients. A suppression of cell proliferation and tumor growth was obtained in MGC803 and HGC-27 cells treated with Linc00152 shRNA. RNA pull-down and RIP assay revealed that Linc00152 could directly bind with EGFR which caused an activation of PI3K/AKT signaling. Conclusion We first found that Linc00152 could promote tumor growth through EGFR-mediated PI3K/AKT pathway which may serve as potential targets for therapy in the future.